The potential of spatial economic theories in studying municipalities’ economic well-being - Elizaveta A. Belousova (Journal of New Economy)
The interdisciplinary nature of modern economic research contributes to the growing scientific popularity of spatial economics, which performs as an integrator when exploring various objects. The paper aims at investigating the explanatory potential of spatial economics in relation to the economic well-being of municipalities. Methodologically the study relies on a host of theories forming the foundation of spatial economics. The methods include the abstract logical method, deduction and induction. The study identifies and analyses five stages in the evolution of the theoretical basis of spatial economics and shows the spatial aspect of creating municipalities’ economic well-being, which manifests itself in maintaining the economic activity in the territory as well as its population and is based on the reproduction process. The reproduction process then is a space-forming one, while such parameters as distance (connectedness), (dis)advantages of location, and distribution (concentration) reflect spatial inclusiveness of a municipality, presence of objects either increasing the risks of its development or its attractiveness, and the limits of territorial capacity, respectively. These parameters can also be applied to determine the level of municipalities’ economic well-being. The findings may underlie the development of a research methodology and a method for measuring the level of municipalities’ economic well-being.